Tinjauan Hukum Islam terhadap Pinjaman Shopeepaylater - Dewi Ulfa, Retno; Kushidayati, Lina (Sharia Faculty Islamic Economic Law Study Department, 2022)
With the rapid development of technology, an application for online shopping (marketplace) was born. One of the largest in Indonesia is the Shopee marketplace. In the Shopee application there is a payment feature that can be made in stages, known as Spaylater. In this study, the theory used is the sale and purchase contract, loan contract, hiwalah contract and usury. This research uses the type of field research or field studies using a qualitative approach. This research was conducted on the Shopee application, where in the Shopee application there is an online loan feature called Spaylater. This feature makes it easy for users to make transactions, because Spaylater itself offers bailouts for users who want to transact but do not have cash. Then the researchers used primary data obtained from interviews with informants in accordance with the research problem. While secondary data, researchers obtained from books, journals, articles from the internet, DSN-MUI Fatwa and theories related to Islamic law. Then for the data collection method using observation, interviews and documentation. The results of this study indicate that if the activation of the Spaylater user is successful, the user can use the limit that has been given. Then regarding the view of Islamic law, looking at Spaylater, namely in the Spaylater mechanism there are conditions for contracts that are not fulfilled in Spaylater. Because in it there is a late fee given by the Spaylater, this late penalty is included in usury jahiliyah. Therefore the practice of Spaylater is not allowed in Islam because it contains elements of usury.